Noise Traders and Herding Behavior - Redding, Lee (IMF Working Papers; Working Paper, 1996)
Recent developments in financial economics have included many explorations into market microstructure, that is, the internal functioning of markets and the ways in which they provide liquidity to traders. An important contribution of this literature is that prices can deviate from their fundamental values. This paper describes models of imperfect liquidity and improperly processed information in financial markets, focusing on the noise trader and investor herding literature. The motivations for this line of research are presented, followed by a description of some of the major contributions and tests of some of their empirical implications.